Leitura e prática pedagógica no ensino médio integrado: contribuições da clínica da atividade - Souza, Adriana Nunes de (2018)
This PhD research in Education, within the research line of Education and language, focuses on the analysis of the report of three professors who work at the Federal Institute of Alagoas. The objective of this work is to understand, through the meanings and meanings attributed by teachers of technical disciplines of Integrated Higher Education, the pedagogical practices of reading and their implications in the teaching-learning process. For that, we discussed Law 11,812 / 08 which created the Federal Institutes, the Integrated High School, the interdisciplinarity, the study reading. We have adopted as a theoretical reference the Social-Historical Psychology of Vygotsky (1991, 1994, 2000), the Clinic of the Activity of Yves Clot (2001,2006,2010), Reading from the perspective of Castello-Pereira (2005) and Leffa (1996) and interdisciplinarity in the perspective of Fazenda (1996, 2001, 2012, 2014). The research was made necessary by the constant complaints of teachers in the technical area that students can not read, that they have difficulty understanding; reading is, for teachers, an obstacle to the teaching-learning process. During the research, we filmed the lectures of three professors of technical subjects in a Campus of the Federal Institute of Alagoas and we discussed their practices in initial interviews and of autoconfrontation. For the analysis of the data, we consider some categories: language and thought, subjective dimension, meanings and meanings, activity real and real activity, gender and style. Thus, we defined pre-indicators, indicators and nuclei of meaning that allowed us to analyze the meanings and meanings attributed and how they appear in pedagogical practice. The data showed that the reading is defined with foundation for the teaching, but it is not worked in an effective way by the teachers; allowed to conclude that self-confrontation makes possible a re-evaluation of the teaching work; made possible the recognition of reading as a facilitator of the learning of the technical subjects and demonstrated that there is a distance between the social and the individual in the pedagogical activity. We could conclude that teachers attribute to reading a foundation role for Integrated Higher Education, but they face obstacles in ordering to achieve this role in their practice. Therefore, we discuss, throughout the thesis, the reading and the interdisciplinarity in the pedagogical practice in the Integrated High School.